The Vicksburg Campaign, March 27-May 18, 1863 - Grear, Charles D., 1976-; Woodworth, Steven E. (Civil War campaigns in the heartland, 2013)
Ulysses S. Grant's ingenious campaign to capture the last Confederate stronghold on the Mississippi River was one of the most decisive events of the Civil War and one of the most storied military expeditions in American history. The ultimate victory at Vicksburg effectively cut the Confederacy in two, gave control of the river to Union forces, and delivered a devastating blow from which the South never fully recovered. Editors Steven E. Woodworth and Charles D. Grear have assembled essays by prominent and emerging scholars, who contribute astute analysis of this famous campaign's most.